Capability of Radial- and Convex-Arrayed Echoendoscopes for Visualization of the Pancreatobiliary Junction - Yoshihide Kanno; Kei Ito; Shinsuke Koshita; Takahisa Ogawa; Hiroaki Kusunose; Kaori Masu; Toshitaka Sakai; Toji Murabayashi; Sho Hasegawa; Fumisato Kozakai; Yujiro Kawakami; Yuki Fujii; et al. (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims Although both radial- and convex-arrayed endoscopic ultrasonography (EUS) scopes are widely used for observational EUS examinations, there have been few comparative studies on their power of visualization. The aim of this study was to evaluate the capability of these EUS scopes for observation of the pancreatobiliary junction. Methods The rate of successful visualization of the pancreatobiliary junction was retrospectively compared between a radial-arrayed and a convex-arrayed echoendoscope, from a prospectively maintained database. Study periods were defined as January 2010 to December 2012 for the radial group, and February 2015 to October 2016 for the convex group because the respective scope was mainly used during those periods. Results During the study period, 1,660 cases with radial EUS and 1,984 cases with convex EUS were recruited. The success rates of observation of the pancreatobiliary junction were 80.0% and 89.5%, respectively (p<0.0001). Conclusions The capability of visualization of the pancreatobiliary junction in observational EUS was found to be better with a convex-arrayed than with a radial-arrayed echoendoscope.